Review of Low-Income Country Debt Sustainability Framework and Implications of the Multilateral Debt Relief Initiative (MDRI). (Policy Papers; Policy Paper ;, 2006)
This paper reviews the experience with the joint IMF-World Bank Debt Sustainability Framework for low-income countries, including cooperation between the staffs, and highlights the implications of the Multilateral Debt Relief Initiative.